Theological education, spiritual formation and leadership development in Africa: What does God have to do with it? - Knoetze, Johannes J. (HTS teologiese studies, 2022)
Theological education, spiritual formation and leadership are all contested issues in the Church, especially within the African context. Although these topics are thoroughly discussed, the relation and the interdependence are not always clear. This article discusses these topics in relation to each other and in relation to the One who calls servant leaders to guide his church for her service in the world. The importance of the local church as missional church is emphasised in the article. Thus, what the faith community believes and teaches about God determines our ecclesiology, theological education and leadership. What does God have to do with theological education, spiritual formation and leadership development in Africa? The answer is everything! The article used a literary study to research the relationship between the different topics and the church and concluded that dependence exists between them.Contribution: Much is written on theological education in Africa. However, students come into theological education with an already established spirituality formed by other agents. The article contributes to the discussion about the relation between formal theological, spiritual formation and leadership. It emphasises the relation between the theological institution and the local church.